Structural Equation Modeling on Health-related Quality of Life of Patients with Ankylosing Spondylitis - Ae Ri JANG; Keum Seong JANG (Iranian Journal of Public Health, 2017)
Background: Ankylosing Spondylitis (AS) is a chronic, progressive, and inflammatory disease. The objective of this study was to construct a hypothetical model to determine factors affecting health-related quality of life (HRQOL) of AS patients (ASHRQOL).